O23.1 Sexual Risk Trajectories Among MSM in the United States: Implications For PrEP Delivery. (13th July 2013) - Pines, H A; Gorbach, P M; Weiss, R E; Shoptaw, S; Ostrow, D G; Stall, R D; Plankey, M
Abstract : Background: CDC guidelines state that men who have sex with men (MSM) at ongoing high risk of HIV infection should be targeted for pre-exposure prophylaxis (PrEP). Longitudinal data can inform the implementation of these guidelines. Methods: HIV-seronegative MSM enrolled in the Multicenter AIDS Cohort Study at 4 U.S. sites completed ACASIs at semi-annual visits. Behaviors since the last visit from 10/1/2003–9/30/2011 were used to assign participants sexual risk behaviour (SRB) scores ranking their risk level at each visit: (0) no insertive and/or receptive anal intercourse (IAI/RAI), (1) no unprotected IAI and/or RAI (UIAI/URAI), (2) only UIAI, (3) URAI with 1 HIV-negative partner, (4) condom-seropositioning, (5) condom-serosorting, and (6) no seroadaptive behaviours. Group-based trajectory modelling was used to examine SRB scores (< 4 vs. ≥ 4) and identify groups with distinct patterns of sexual risk. Results: The sample (N = 430) was 38.4% White, 42.3% Black, 14.9% Hispanic and had a median age of 39.1 years (IQR = 31.3–44.3). Three trajectory groups were identified: no risk (N = 286; 66.5%), low risk (N = 89; 20.7%), and high risk (N = 55; 12.8%). Compared to the no risk group, high risk group membership was negatively associated with older age (adjusted odds ratio [AOR] for 5-year age difference = 0.68, 95% CI: 0.56–0.84) and positively associated with being White (AOR = 2.12, 95% CI: 0.97–4.62), earning an income ≥$20, 000 (AOR = 4.96, 95% CI: 2.10–11.71), depression (CESD≥ 16) (AOR = 2.06, 95% CI: 0.98–4.31), and stimulant use (AOR = 2.37, 95% CI: 1.18–4.78) at the index visit. Adjusted group membership probabilities for a 30 year-old, White male reporting an income ≥$20, 000, depression, and stimulant use at the index visit were 0.15 (no risk), 0.39 (low risk), and 0.46 (high risk). Conclusion: Findings suggest MSM following high risk trajectories could be identified by the socio-demographic and behavioural factors described above, thus enabling PrEP programmes to target those at ongoing high risk of HIV infection.